2008
DOI: 10.1093/ndt/gfn631
|View full text |Cite
|
Sign up to set email alerts
|

Role of medication in the level of aluminium in the blood of chronic haemodialysis patients

Abstract: Among the medications investigated, the injectables are the most significant source of aluminium for patients with renal insufficiency. This extra aluminium intake is reflected in higher aluminium levels in the patients' blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…The median aluminum concentration in 5% glucose solutions was 5 ng/g. 9 The aluminum concentration has been reported in numerous drugs, 34,35 but in only 3 medications similar to those used in the present study. The median aluminum concentration in electrolyte and flavored electrolyte solutions was 5 ng/g, comparable to the 6.2 mcg/L of the present study.…”
Section: Discussionsupporting
confidence: 52%
“…The median aluminum concentration in 5% glucose solutions was 5 ng/g. 9 The aluminum concentration has been reported in numerous drugs, 34,35 but in only 3 medications similar to those used in the present study. The median aluminum concentration in electrolyte and flavored electrolyte solutions was 5 ng/g, comparable to the 6.2 mcg/L of the present study.…”
Section: Discussionsupporting
confidence: 52%
“…However, these newly developed medications have not become popular in many countries due to their high cost [20]. In addition, the source of aluminium may contribute to extra aluminium intake from other medications [21]. Therefore, aluminium overload is still a potential problem among the dialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 319 HD patients, 14 patients used oral Al(OH) 3 to control serum phosphate and three had serum Al higher than 250 μg/L. Ingested Al(OH) 3 is not the only source of Al that Bohrer et al (2009) found for patients with kidney disease, because injectable drugs (notably insulin, EPO, and Fe) were also significant Al sources. Jimenez et al (2011) concluded that Al-based phosphate binders could be used but in light of the risks for adynamic bone disease other measures (reduced dietary phosphate and increased dialysis duration) should be exhausted prior to considering use of Al-based phosphate binders.…”
Section: Environmental and Occupational Exposurementioning
confidence: 99%